INVESTIGATIONS OF PUMPED-STORAGE HYDRO PLANTS IN THE ALPINE AREA - Lasminto, Umboro; Klasinc, Roman (Journal of Energy Technology, 2024)
One target of the European Union (EU) countries is that 20% of energy be supplied by renewable sources by 2020. To achieve this target, renewable energy production from wind power, solar power, hydro power, tidal power, geothermal and biomass should be increased. However, the production of energy from renewable energy is not at constant level, so it often does not meet demand, especially during periods of peak demand. Another factor in the rising demand for peak energy is the changing conditions of the European energy market. Therefore, energy storage is required to fulfil peak energy demand. A pumped storage plant is the most significant solution for storing and generating energy. There are some new pumped storage plants (PSP) in the Alpine area in Austria and Germany, such as Kops II, Limberg II, Reisseck II and Atdorf-Schluchseewerk. In this paper, the authors will present an overview of the new PSPs, the hydraulic problems that arise in the construction of PSPs, and some investigations and studies using scale models and numerical analysis in order to solve the problem.